Potential Uses of ERS-1 SAR Data For The Malaysian Coastal Zone - Seeni Mohd, Mohd Ibrahim; Ahmad, Samsudin; Hoekman, D. H.; Greidanus, H. (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1997)
Satellite remote sensing using visible and infrared wavelengths is not very suitable in the tropics because of the cloud cover problem. Radar remote sensing can overcome this problem although it may not possess some of the advantages of sensing in the optical wavelengths.